Saara: uma paisagem singular na cidade do Rio de Janeiro - 1960-1990 - Ribeiro, Paula (2000)
This research is an interdisciplinary analysis and it focuses on the Saara , a commercial district in downtown Rio de Janeiro. I have attempted to analyze this area, as a dynamic space, in constant transformation, composed of social members who integrate with it, making it a part of the city with a unique character. Notable for the presence of Arabs (Syrians and Lebanese) and Jews in the city, the approach of this research considers the experiences and social practices which these immigrants and descendants have developed in the context of the area known as Saara , with its own territorial characteristics marked by the culture of its inhabitants origins. Considering memory as an important dimension, special attention is given to how the occupants of Saara have constructed it and have altered it in a complex and ambiguous way, expressing a dispute for a place, in the culture and for culture itself